A utilização do site de redes sociais de internet Facebook em campanhas eleitorais : um estudo de caso a partir da campanha eleitoral para governador de Sergipe em 2014 - Balbino, Ivan Kelleros (2017)
According to the data released by Facebook in 2016, counting 99 million users only in Brazil, social networks have grown in size and importance in the mobilization of several themes, including electoral politics. Since 2008, with the presidential campaign of Barack Obama in the USA, social networks on the internet have gained space on the political scene and had been officially and legally incorporated in the Brazilian election process of 2010. Since then, such use, especially of Facebook, has gained the attention of political-party campaign managers. This case study investigates the use of Facebook in the election campaign for governor of Sergipe, in 2014, by the candidate Jackson Barreto and has as locus of research the timeline of the candidate's fan page. It is important to reflect on the potentialities of the use that Facebook provides and how it was used by the candidate here analyzed, identifying types of posts, interaction and used themes. The specific objectives: (i) identify the transformations, in the field of communication, those social networking sites wich provide for their users - candidates and voters - in electoral campaigns; (Ii) to categorize data and indicators of the Facebook fan page of the candidate elected to governor of the Province of Sergipe, during the electoral period of 2014, evidencing the use of the refered social networking site for broader and electoral communication purposes; (Iii) analyze the content of the candidate's posts and the interaction generated in his fan page, in order to qualify the use of the Facebook platform concerning to electoral communication. The methodological delineation of this qualitative-quantitative research relies on content analysis as a complementary procedure to the case study, carried out through the candidate's postings identified during the electoral period of 2014. It is known that Facebook offers a dynamic platform for a considerable variety of interactions and campaign actions of the candidate, often reaching a very large number of voters The results of the case studied point to: (i) the receiver's willingness to interact with the devices to enjoy, share and comment; (Ii) a small number of posts during the campaign period; and (iii) post content that made the Facebook candidate a non-digital campaign mirror.